Initial activation state, stimulation intensity and timing of stimulation interact in producing behavioral effects of TMS. (5th November 2017) - Silvanto, Juha; Bona, Silvia; Cattaneo, Zaira
Highlights: TMS effects depend on various factors such as intensity, brain state and timing. We examined how these factors interact to give rise to behavioral effects. TMS was applied while participants performed a behavioral priming task. State dependency of TMS effect was found to interact with intensity and timing. Abstract: Behavioral effects of transcranial magnetic stimulation (TMS) have been shown to depend on various factors, such as neural activation state, stimulation intensity, and timing of stimulation. Here we examined whether these factors interact, by applying TMS at either sub- or suprathreshold intensity (relative to phosphene threshold, PT) and at different time points during a state-dependent TMS paradigm. The state manipulation involved a behavioral task in which a visual prime (color grating) was followed by a target stimulus which could be either congruent, incongruent or partially congruent with the color and orientation of the prime. In Experiment 1, single-pulse TMS was applied over the early visual cortex (V1/V2) or Vertex (baseline) at the onset of the target stimulus – timing often used in state-dependent TMS studies. With both subthreshold and suprathreshold stimulation, TMS facilitated the detection of incongruent stimuli while not significantly affecting other stimulus types. In Experiment 2, TMS was applied at 100 ms after target onset –a time window in which V1/V2 is responding to visual input. Only TMS applied at suprathreshold intensity facilitated the detection of incongruent stimuli, with no effect with subthreshold stimulation. The need for higher stimulation intensity is likely to reflect reduced susceptibility to TMS of neurons responding to visual stimulation. Furthermore, the finding that in Experiment 2 only suprathreshold TMS induced a behavioral facilitation on incongruent targets (whereas facilitations in the absence of priming have been reported with subthreshold TMS) indicates that priming, by reducing neural excitability to incongruent targets, shifts the facilitatory/inhibitory range of TMS effects.